PENGARUH PENDIDIKAN, PENGALAMAN DAN FAKTOR SOSIAL TERHADAP PEMANFAATAN INFORMASI LAPORAN ARUS KAS DI KECAMATAN EROMOKO, KABUPATEN WONOGIRI - Anik Wahyuni; Hadi Samanto; Maya Widyana Dewi (ITB AAS INDONESIA, 2023)
The research aims to analyze the effect of education, experience, and social factors on the use of cash flow statement information in Eromoko District, Wonogiri Regency. This research is a type of quantitative descriptive research using a questionnaire as a valid and reliable research instrument. Samples were taken from 97 people from the Basuhan village community by simple random sampling. Methods of data analysis using instrument test, descriptive statistical test and classical assumption test. Testing the hypothesis using multiple linear regression analysis. The results showed that education, experience, and social factors influenced the utilization of cash flow statement information with a coefficient of determination of 0,631. This means that 63,1% of variations in changes in the use of cash flow statement information can be explained by variations in education, experience, and social factors. While the remaining 36,9% was explained by other factors outside of this study. Keywords : education, experience, social factors, utilization of cash flow statement information.